EFFICACY OF EUPHORBIA HETEROPHYLLA LATEX AGAINST PATHOGENIC BACTERIA AND FUNGI - ML, PRUTHVI; MK, MAHESH; SAHAYA MARY, ROHINI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to determine the antimicrobial activities of Euphorbia heterophylla latex. Methods: The antibacterial and antifungal activities of acetone, chloroform, and diethyl ether extracts were assayed by disk diffusion method. Results: The study of plant E. heterophylla latex revealed the presence of medically active metabolites. Bacterial strains such as Staphylococcus aureus, Bacillus subtilis, Proteus vulgaris, and Pseudomonas aeruginosa exhibited a strong zone of inhibition. Acetone extract exerts a potent zone of inhibition against P. aeruginosa compared to tetracycline. Fungi, Aspergillus niger, Fusarium oxysporum, and Penicillium sp., were used for the antifungal activity. It was observed that the highest zone of inhibition was noticed against A. niger in all the extracts. Interestingly, F. oxysporum and Penicillium sp. showed no zone of inhibition and were resistant to standard drug, fluconazole which was used as a control. Conclusion: E. heterophylla latex extract was found to be more potent than the standard drugs which were used against both the bacterial and fungal strains.